Clinical effectiveness of scleral taping combined with perfluoropropane for complex retinal detachment - Wang, Xin; Li, Chen; Liu, Linlin; Xie, Linying; Jiang, Yiping (Frontiers in Medicine, 2025)
PurposeThis study evaluated the effectiveness of scleral taping combined with C3F8 gas filling for the management of complex retinal detachment (CRD) and to objectively assessed its clinical value.MethodsForty consecutive patients (40 eyes) with CRD who underwent surgical treatment were included. Patients were divided into two groups: the study group underwent scleral buckling (SB) combined with C3F8 gas filling, and the control group received scleral buckling alone. Each group comprised 20 patients (20 eyes). After anaesthesia, traction sutures were placed at the rectus muscle in all patients. Retinal breaks and degenerative areas were examined and treated with cryotherapy. A silicone sponge was positioned on the scleral surface, and the sutures were tightened to produce an indenting effect. Additionally, patients in the study group received an intravitreal injection of C3F8 gas.ResultsBoth uncorrected visual acuity (UCVA) and best-corrected visual acuity (BCVA) improved in the study and control groups on the first post-operative day. However, the improvement was statistically significant only in the control group. Visual acuity in both groups improved significantly at 1 week, 1 month, and 3 months post-operatively compared with baseline and the first post-operative day. Intraocular pressure (IOP) in the study group was significantly elevated at 1 week, 1 month, and 3 months post-operatively compared with baseline. The retinal reattachment rate was 95% in the study group, significantly higher than 70% in the control group. The recurrence rate was 5% in the study group. No serious complications, including retinal incarceration, haemorrhage, anterior segment ischemia, or infection, were observed in either group.ConclusionScleral buckling combined with C3F8 gas filling is a safe and effective treatment for CRD. It significantly improves post-operative visual acuity, enhances retinal reattachment, reduced the recurrence rate with minimal complications.